2013
DOI: 10.1051/0004-6361/201321045
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of new companions to high proper motion stars from the VVV Survey

Abstract: Context. The severe crowding in the direction of the inner Milky Way suggests that the census of stars within a few tens of parsecs in that direction may not be complete. Aims. We searched for new nearby object companions of known high proper motion (HPM) stars located towards the densest regions of the southern Milky Way where the background contamination presented a major problem to previous observations. Methods. The common proper motion (PM) method was used. We inspected the area around 167 known HPM (≥200… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…This is the high-PM star LTT 6467 with a low metallicity [Fe/H] = −0.78. Ivanov et al (2013) found no CPM companions.…”
Section: Newly Resolved Pairsmentioning
confidence: 89%
“…This is the high-PM star LTT 6467 with a low metallicity [Fe/H] = −0.78. Ivanov et al (2013) found no CPM companions.…”
Section: Newly Resolved Pairsmentioning
confidence: 89%
“…The VVV is a variability survey primarily designed to trace the 3-D structure of the Milky Way, observing 562 •2 towards the Galactic Bulge and southern inner disk (Gonzalez et al 2011;Dékány et al 2013;Minniti et al 2014). This survey matches the requirements for good estimations of the proper motions (PMs) and parallaxes, as demonstrated previously by Beamín et al (2013); Ivanov et al (2013). The data were reduced at the Cambridge Astronomy Survey Unit (CASU) with pipeline v1.3.…”
Section: Magellan/firementioning
confidence: 99%
“…The CPM method continues to be useful, in particular for new deep surveys (e.g. Ivanov et al 2013;Deacon et al 2014). Focusing on a sample of nearby F stars, we demonstrate how much we can still improve the CPM statistics and find previously overlooked wide companions, even of wellknown bright stars, in existing public surveys.…”
Section: Introductionmentioning
confidence: 85%